2021
DOI: 10.3390/app112311364
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Pedestrian Crash Model Based on Artificial Intelligence Techniques

Abstract: Every year in Italy, there are about 20,000 road accidents involving pedestrians, with a significant number of injuries and deaths. Out of these, about 30% occur at pedestrian crossings, where pedestrians should be protected the most. Here, we propose a new accident prediction model to improve pedestrian safety assessments that allows us to accurately identify the sites with the largest potential safety improvements and define the best treatments to be applied. The accident prediction model was developed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Logistic regression models have been seen in the literature [ 36 38 ], along with a range of machine learning techniques, such as regression trees, random trees, random forests, support vector machines, k-nearest neighbors, and deep neural networks [ 39 44 ]. In addition to count data and categorical data, there is considerable interest in the traffic congestion rate.…”
Section: Introductionmentioning
confidence: 99%
“…Logistic regression models have been seen in the literature [ 36 38 ], along with a range of machine learning techniques, such as regression trees, random trees, random forests, support vector machines, k-nearest neighbors, and deep neural networks [ 39 44 ]. In addition to count data and categorical data, there is considerable interest in the traffic congestion rate.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by [24], researchers address the pressing issue of pedestrian safety in traffic accidents, particularly in Italy. Every year in Italy there are approximately 20,000 traffic accidents involving pedestrians, with a significant proportion (approximately 30%) occurring at pedestrian crossings, where pedestrians should ideally be most protected.…”
Section: Related Workmentioning
confidence: 99%
“…An analysis of the Italian historical accident data (2014–2018) conducted by Meocci et al, in 2021 [ 7 ] revealed that 30 % of traffic collisions involving pedestrians occur at pedestrian crossings, which should be the safest place for pedestrians that are crossing the street. Therefore, it is necessary to seriously understand the factors affecting the phenomenon and provide effective solutions that reverse the trend and mitigate this issue worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…A possible approach to research this topic is the passive approach, which is based on the analysis of crash database in order to identify of both crash-prone locations and factors affecting the phenomenon [ 7 , [21] , [22] , [23] , [24] ]. However, this approach fails to go into detail and does not investigate the crash environment or the road characteristics approaching the site of the crash [ 25 ] and often does not consider driving speed as a variable.…”
Section: Introductionmentioning
confidence: 99%